A population dynamic model to assess the diabetes screening and reporting programs and project the burden of undiagnosed diabetes in Thailand - Mahikul, W; White, L; Poovorawan, K; Soonthornworasiri, N; Sukontamarn, P; Chanthavilay, P; Pan-Ngum, W; Medley, G (MDPI, 2019)
Diabetes mellitus (DM) is rising worldwide, exacerbated by aging populations. We estimated and predicted the diabetes burden and mortality due to undiagnosed diabetes together with screening program efficacy and reporting completeness in Thailand, in the context of demographic changes. An age and sex structured dynamic model including demographic and diagnostic processes was constructed. The model was validated using a Bayesian Markov Chain Monte Carlo (MCMC) approach. The prevalence of DM was predicted to increase from 6.5% (95% credible interval: 6.3-6.7%) in 2015 to 10.69% (10.4-11.0%) in 2035, with the largest increase (72%) among 60 years or older. Out of the total DM cases in 2015, the percentage of undiagnosed DM cases was 18.2% (17.4-18.9%), with males higher than females (p-value < 0.01). The highest group with undiagnosed DM was those aged less than 39 years old, 74.2% (73.7-74.7%). The mortality of undiagnosed DM was ten-fold greater than the mortality of those with diagnosed DM. The estimated coverage of diabetes positive screening programs was ten-fold greater for elderly compared to young. The positive screening rate among females was estimated to be significantly higher than those in males. Of the diagnoses, 87.4% (87.0-87.8%) were reported. Targeting screening programs and good reporting systems will be essential to reduce the burden of disease.